Current Status and Factors Influencing Surgical Options for Breast Cancer in China: A Nationwide Cross‐Sectional Survey of 110 Hospitals. (13th May 2020) - Yang, Benlong; Ren, Guosheng; Song, Erwei; Pan, Da; Zhang, Jing; Wang, Yongsheng; Liao, Ning; Tang, Jinhai; Wang, Xiang; Cui, Shude; Jin, Feng; Geng, Cuizhi; et al.
Abstract: Background: There are limited nationwide data regarding breast cancer surgery in China. The Chinese Anti‐Cancer Association's Committee of Breast Cancer Society and the Chinese Society of Breast Surgeons conducted a nationwide survey to examine the use of and barriers associated with surgical options among patients with breast cancer. Methods: Surveys were sent via e‐mail to the directors of 110 centers that performed at least 200 breast cancer operations in 2017. The electronic questionnaire contained 183 questions and covered six aspects, including demographic information about the hospitals and surgeons, surgical practice, and application of breast reconstruction. Results: The selected hospitals were from 31 provinces or municipalities. The overall proportion of breast‐conserving surgery (BCS) was 22%. Local gross domestic product was significantly related to the rate of BCS ( p = .046). Sentinel lymph node biopsy was performed routinely in 76% of hospitals. Only 14.5% (16/110) of hospitals used the dual‐tracer method, including radioisotopes. For patients with cN0 disease receiving BCS with one or two positive sentinel lymph nodes, 20% (22/110) of hospitals accepted omitting axillary lymph node dissection (ALND). For patients who underwent mastectomy, only 4% (4/110) of hospitals accepted omitting ALND. There was an obvious polarization trend in the proportion of oncoplastic breast‐conserving surgery (OPS); 35/110 (32%) performed OPS in fewer than 10% of cases, whereas 36/110 (33%) performed OPS in more than 50% of cases. OPS was more likely to be performed in academic hospitals. Volume displacement was more commonly used than volume replacement ( p < .001). Breast reconstruction was routinely performed in 96/110 (87%) of hospitals, 62% of which involved cooperation with the plastic surgery department. Factors influencing breast reconstruction after mastectomy included the establishment of a plastic surgery department, regional economy, and cooperation between the plastic and general surgery departments. Overall, the proportion of breast reconstruction procedures after mastectomy was 10.7%, with 70% being implant‐based reconstruction, 17% autologous tissue reconstruction, and 13% a combination. Overall, 22% of the hospitals predominantly performed immediate breast reconstruction. For delayed reconstruction, two‐stage implant‐based breast reconstruction was the first choice for 46% of centers, whereas 20% of centers chose autologous reconstruction. Among the 96 centers that performed autologous‐based reconstruction, 96% performed latissimus dorsi flap reconstruction, 65% performed transverse rectus abdominis musculocutaneous flap reconstruction, and 45% used deep inferior epigastric artery perforator flaps. Conclusion: The results are of great value for promoting the implementation of a consensus on diagnostic and treatment standards, development of guidelines for breast cancer, and training of breast specialists. Abstract : On the basis of a survey that examined the use of breast cancer surgical options in hospitals across China, this article reports statistics on clinical treatments and surgeries, the distribution of clinical stages, and demographic characteristics of patients, in order to establish comprehensive baseline data on the current status of breast cancer treatment in China.